The genus Anterhynchium in the Philippine Islands (Hymenoptera: Vespidae, Eumeninae) - Marco Selis (Fragmenta entomologica, 2017)
A taxonomic study on the genus Anterhynchium de Saussure, 1863 from the Philippine Islands is presented. Two species are recorded: A. astrophilum Giordani Soika, 1996 and A. townesi van der Vecht, 1963. Anterhynchium astrophilum is recorded for the first time since its description, A. flavomarginatum townesi is raised to species rank (A. townesi stat. nov.) and its unknown male is described. A key to the species and new distributional records are provided.